A New Reference Plasmid "pGMT27" Provides an Efficient Transgenic Detection Method for Flue-Cured Tobacco. (15th November 2021) - Yu, Jing; Zhang, Xiaolian; Adil, Muhammad Faheem; Lei, Bo; Jia, Mengao; Zhao, Huina; Yu, Shizhou; Liu, Jiemin; Guo, Yushuang; Shamsi, Imran Haider
Abstract : Owing to the economic value of its foliage, tobacco ( Nicotiana tabacum ) is cultivated all across the world. For the detection of genetically modified (GM) tobacco, there is a lack of universal standard material which ultimately limits the detection methods because the accuracy and comparability of the results cannot be ensured. Here, we prepared a reference plasmid "pGMT27" for the detection of GM tobacco, which was 18, 296 bp in length harboring two of the tobacco endogenous and seven exogenous genes. By using qualitative PCR test for the nine genes, 10 copies were used for plasmid sensitivity. In the quantitative real-time PCR (qPCR) assays with pGMT27 as a calibrator, the reaction efficiencies for P-35S and NR were 101.427% and 98.036%, respectively, whereas the limit of detection (LOD) and limit of quantification (LOQ) were 5 copies and 10 copies per reaction. For standard deviation (SD) and relative standard deviation (RSD) of the Ct values, the repeatability values were from 0.04 to 0.42 and from 0.18% to 1.29%, respectively; and the reproducibility values were from 0.04 to 0.39 and from 0.18% to 1.14%, respectively. For the unknown sample test, the average conversion factor (Cf) was 0.39, and the accuracy bias was from −15.55% to 1.93%; for precision, the SD values ranged from 0.02 to 0.62, while RSD values were from 1.34% to 10.6%. We concluded that using the pGMT27 plasmid as a calibrator provided a highly efficient transgenic detection method for flue-cured tobacco.